1982
DOI: 10.1111/j.2044-8279.1982.tb02509.x
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Ideational Fluency: Some Normative Data

Abstract: Summary. 199 schoolchildren in five groups at 1‐year intervals between the ages of 7 and 12 completed a verbal and a figural divergent test along with the Draw‐a‐Man test in a preliminary normative investigation of age trends in ideational fluency. The broadly consistent increases with age found on the verbal divergent and Draw‐a‐Man tests were not present on the figural divergent test, and there were no consistent effects of sex on these results. Further normative data are needed to clarify the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
2
2
0
Order By: Relevance
“…It seems fair to conclude that perceived creativity increases with the age of the artist, as long as the rater does not know the age of the artist. This finding is in keeping with previous findings of increased creativity with age [26][27][28], while it casts doubt on the validity of claims by Gardner [25] and Winner [29] that children's drawings decrease in creativity with age. It is, furthermore, in keeping with objective measures of the use of symmetry and three-dimensional cues in Experiment 2, where greater use of these structural forms in adults' drawings would seem to indicate that even untrained adults can draw more sophisticated pictures than can children.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It seems fair to conclude that perceived creativity increases with the age of the artist, as long as the rater does not know the age of the artist. This finding is in keeping with previous findings of increased creativity with age [26][27][28], while it casts doubt on the validity of claims by Gardner [25] and Winner [29] that children's drawings decrease in creativity with age. It is, furthermore, in keeping with objective measures of the use of symmetry and three-dimensional cues in Experiment 2, where greater use of these structural forms in adults' drawings would seem to indicate that even untrained adults can draw more sophisticated pictures than can children.…”
Section: Discussionsupporting
confidence: 89%
“…On the contrary, Dallner [26] and Holland [27] have found ratings of creativity of children's drawing, coloring, and story writing to increase with age. Furthermore, Hargreaves has found that scores on tests of fluency, often considered to be a measure of creativity, increase with age [28]. The drawings obtained in Experiment 2 showed the increased use of more sophisticated visual structure by untrained adults.…”
Section: Methodsmentioning
confidence: 90%
“…| 2015 | ISSUE 2 | VOLUME 10 © 2015 University of Alicante The behaviour of total fluency, which increased very little between Levels 2 and 3, appears to corroborate the existence of what authors such as Torrance (1968) and Hargreaves (1982) have called "the fourthgrade slump". Similarly, the marked increase between Levels 1 and 2 is in keeping with the reports of significant advances between ages 7 and 8 years (Torrance, 1981;Cleland & Gallahue, 1993).…”
supporting
confidence: 48%
“…Although experimental practices from the group and decision support system literature were reviewed rather extensively, design aspects from the psychology literature were only cursorily considered. Within the psychology literature, ideational fluency--the ability of an individual to generate ideas (Torrance 1990)--has long been considered a significant, relevant independent variable impacting creative performance (see, for example, Frederiksen and Evans 1974;Hargreaves 1982;Hocevar 1979;Houtz and Speedie 1978;Milgram 1983;Milgram and Arad 1981;Sawyers et al 1983). Traditionally, it has been accounted for within the psychology literature by recording the number of non-redundant ideas an individual generates before and after various treatment conditions.…”
Section: Research Design and Cssmentioning
confidence: 99%